Tinjauan Yuridis Perlindungan Hukum Pemberian Kredit Usaha Rakyat (Kur) Kepada Masyarakat Di Bank Rakyat Indonesia (Bri) - Surianingrat, Aji; , Inayah, S.H., M.H (2016)
This study aims to find out the People's Business Credit (KUR) Micro and the impact of KUR in alleviating poverty, and to investigate legal action against borrowers who have problem loans. The research method using empirical juridical approach (non-doctrinal) the nature of the descriptive study. Data sources include primary data, interviews and secondary data sources include primary and secondary law. Data were collected by literature study and interviews. Data were analyzed using qualitative analysis. The results showed that the credit approval process still refers to the mechanism in accordance with applicable regulations and keep promoting the principle of prudence. People's Business Credit a significant impact on poverty reduction, in accordance with the government's objective is to develop the standard of living in accordance with the viability and provide welfare to society. Legal efforts in addressing problem loans are charging continuously through methods Mantri / Account Office came to the house of the debtor to discuss amicably or more persuasive, by mail / in writing billing and billing through the team.